The Contribution of the Umayyad Dynasty to the Development of Civilization and the Advancement of Islamic Education - Bulqis Bulqis; Muhammad Fadhil Hadziq (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The Umayyad Dynasty (661–750 CE) played a significant role in the history of Islamic civilization, not only through territorial expansion but also in the development of education as a foundation for civilizational progress. This study aims to analyze the contributions of education during the Umayyad era, the roles of intellectuals and scholars, and the integration of religious and worldly knowledge in shaping competent human resources. The research employs a qualitative approach with historical and comparative analysis, examining historical documents, classical manuscripts, academic literature, and previous studies on Islamic education of the period. The findings indicate that Umayyad education was structured through kuttabs, madrasas, halaqahs, bimaristans, and literary councils, covering religious sciences as well as general disciplines such as mathematics, astronomy, medicine, and philosophy. The use of Arabic as a lingua franca strengthened knowledge dissemination. These educational initiatives facilitated the advancement of Islamic civilization by establishing intellectual centers in Damascus, Basra, Kufa, and Andalusia. In conclusion, education during the Umayyad period was not merely formal instruction but a strategic foundation for Islamic civilization, integrating religious and worldly knowledge. This study contributes by highlighting education as a primary pillar of civilizational development in the classical Islamic era.